Pengaruh Rasio Likuiditas, Profitabilitas, Dan Aktivitas Terhadap Nilai Perusahaan Pada Industri Dasar & Kimia Subsektor Plastik & Kemasan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2018-2022 - Kurniawan, Airlangga Hafizh; Permata, Irma Sari; Heriansyah, Kurnia (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The high business competition that occurs in the basic and chemical industries of the plastics and packaging sub-sector also encourages companies to develop their businesses in order to obtain greater profits, one of which is by attracting investor interest through financial performance, which can be seen through liquidity and profitability ratios and activity ratios. The purpose of this study was to determine and analyze the effect of liquidity, profitability, and activity on company value. This research uses a descriptive method with a quantitative approach. Data is collected through literature studies and secondary data from the Indonesia Stock Exchange website. Data analysis techniques include descriptive statistics and multiple linear regression analyses. The results showed that liquidity has an influence and significance on the value of the company. Furthermore, profitability has an influence on the value of the company. While the activity ratio has no influence on the value of the company.